Reduction pathway of end-on terminally coordinated dinitrogen. V. N-N bond cleavage in Mo/W hydrazidium complexes with diphosphine coligands. Comparison with triamidoamine systems - Mersmann, Klaus; Horn, Kay H.; Böres, Natascha; Lehnert, Nicolai; Studt, Felix; Paulat, Florian; Peters, Gerhard; Ivanovic-Burmazovic, Ivana; van Eldik, Rudi; Tuczek, Felix (Inorganic Chemistry, 2005)
N-N cleavage of the dialkylhydrazido complex [W(dppe)(NNC H)] (B) upon treatment with acid, leading to the nitrido/imido complex and piperidine, is investigated experimentally and theoretically. In acetonitrile and at room temperature, B reacts orders of magnitude more rapidly with HNEtBPh than its Mo analogue, [Mo(dppe)-(NNCH)] (B ). A stopped-flow experiment performed for the reaction of B with HNEtBPh in propionitrile at -70°C indicates that protonation of B is completed within the dead time of the stopped-flow apparatus, leading to the primary protonated intermediate BH. Propionitrile coordination to this species proceeds with a rate constant K of 1.5 ± 0.4 s, generating intermediate RCN-BH (R = Et) that rapidly adds a further proton at N and then mediates N-N bond splitting in a slower reaction (K = 0.35 ± 0.08 s, 6 equiv of acid). K and K are found to be independent of the acid concentration. The experimentally observed reactivities of B or B with acids in nitrile solvents are reproduced by DFT calculations. In particular, geometry optimization of models of solvent-coordinated, N-protonated intermediates is found to lead spontaneously to separation into the nitrido/imido complexes and piperidine/piperidinium, corresponding to activationless heterolytic N-N bond cleavage processes. Moreover, DFT indicates a spontaneous cleavage of nonsolvated B protonated at N. In the second part of this article, a theoretical analysis of the N-N cleavage reaction in the Mo(III) triamidoamine complex [HIPTNN]Mo(N) is presented (HIPTNN = hexaisopropylterphenyltriamidoamine). To this end, DFT calculations of the MoN triamidoamine complex and its protonated and reduced derivatives are performed. Calculated structural and spectroscopic parameters are compared to available experimental data. N-N cleavage most likely proceeds by one-electron reduction of the Mo(V) hydrazidium intermediate [HIPTNN]Mo(NNH), which is predicted to have an extremely elongated N-N bond. From an electronic-structure point of view, this reaction is analogous to that of Mo/W hydrazidium complexes with diphos coligands. The general implications of these results with respect to synthetic N fixation are discussed. © 2005 American Chemical Society.